Lignin-first depolymerization of softwood over a NiCu/TiO2 catalyst for the sustainable production of dihydroconiferyl alcohol - Peng Zhu; Yu-Xin Zhang; Qiang Wang; Guo-Hui Cheng; Jun-Li Ren; Ling-Ping Xiao; Run-Cang Sun (Bioresource Technology, 2026)

Environmental cadmium disrupts placental angiogenesis and fetal growth via enhancing m6A modification in Wwp2 - Cheng-Fang Sun; Ye-Xin Luo; Xin-Xin Zhang; Rui Pan; Yu-Xi Wu; Jia-Ying Chen; Xin-Run Wang; Lan-Lan Wu; Si-Ting Liu; Wei Chang; Zhi Yuan; Da-Min Zhu; et al. (Environmental Pollution, 2026)

Extent of soil disturbance and spatial strength degradation induced by spudcan penetration and extraction in clay - Cheng-feng Li; Rui Zhou; Run Liu; Hai-yang Zhang; Peng-cheng Ma (Ocean Engineering, 2026)

An unprecedented alternariol-zinnol hybrid and six undescribed zinnol derivatives from the phytopathogen Alternaria solani and their cytotoxic activities - Ming Hu; Run-Cheng Yan; Qiao-Ling Wei; Jiang-Li Su; Bi-Juan Yang; Wen-Chao Tu; Gan-Peng Li; Xing-De Wu (Phytochemistry, 2026)

Autophagy, ROS, and their interplay in plant adaptive responses - Chi Zhang; Song-Qi Li; Pengwei Jing; Run-Xin Wu; Yu-Qing Ma; Ji-Xiao Wu; Ru-Feng Song; Wen-Cheng Liu (Journal of Plant Physiology, 2026)

A study on soil erodibility and the applicability of estimation methods in Robinia pseudoacacia L. mixed forests on the Loess Plateau, China - Jin-long Ma; Bing Wang; Run-hao Yu; Yan-fen Yang; Guo-bin Liu; Jing Wang; Cheng-fang Li (CATENA, 2025)

Transcriptomic profiling reveals mechanism, therapeutic potential, and prognostic value of cancer stemness characteristic in nasopharyngeal carcinoma - Jin-Wei Chen; Run-Nan Shen; Jiang-Quan Zhu; Ying-Hang Wang; Liang-Min Fu; Yu-Hang Chen; Jia-Zheng Cao; Jin-Huan Wei; Jun-Hang Luo; Jia-Ying Li; Cheng-Peng Gui (Functional & Integrative Genomics, 2025)

Fast Forward Modeling of Resistivity Method under Complex Topography Using Finite Element Method - Zhan Wang; Chang-Wei Li; Yu-Zeng Lv; Run-Lin Luo; Bo Cheng; Bo Li (Applied Geophysics, 2025)

Geological and geochemical characteristics of intermediate-basic intrusions in Funiushan area, southern margin of the North China Craton: Implications for tectonic environment and mantle properties in the Early Cretaceous - Wei Zeng; Feng-Yue Sun; Cheng-Dong Li; Zhi-Dan Li; Yin-Hang Cheng; Wen-Gang Liu; Jia-Run Tu; Chao Zhang; Xing Liu; Wei-Zhi Sun (Lithos, 2025)

Environmental adaptive nanoplatform for bacteriotherapy - Wei Sun; Yang Bai; Xuefei Shao; Bowen Li; Haohua Yuan; Xuheng Chen; Run Yang; Yuan Liu; Shixiang Cheng; Yanguo Xi; Qing-hui Meng; Bin Zheng; et al. (Chemical Engineering Journal, 2025)

Waste biomass-derived organic matter for sustainable soil remediation: Enhancing heavy metal removal and eluent reuse in agricultural application - Shuai Yang; Chen Tu; Guo-ming Liu; Yuan Li; Yi Wang; Xia Zhu; Shao-cheng Si; Run-lai Luo; Zhong-yuan Li; Yong-ming Luo (Bioresource Technology, 2025)

Boosting structural stability and air stability towards layered oxide cathodes for potassium ion batteries - Hong Chen; Lu-Kang Zhao; Xuejiao Cheng; Xuan-Wen Gao; Zhaomeng Liu; She-Dong Li; Dong-Run Yang; Tian-Zhen Ren; Wen-Bin Luo (Chemical Engineering Journal, 2025)

Kopsileuconines A−D: Bisindole alkaloids with cytotoxic activity from Kopsia hainanensis - Ni-Ping Li; Shan-Na Chen; Wei-Fang Su; Fen Liu; Lian-Jing Li; Jian-Guo Song; Min-Jing Cheng; Yi-Yi Li; Run-Qiang Chen; Xue-Ping Lei; Wen-Cai Ye; Lei Wang (Phytochemistry, 2024)

MGDA-assisted plant washing agent for improving the removal of Cd and Cu from farmland soils - Yi Wang; Chen Tu; Yuan Li; Shuai Yang; Ying Liu; Xia Zhu; Shao-cheng Si; Run-lai Luo; Xiang-liang Pan; Yong-ming Luo (Environmental Pollution, 2024)

Aerobic granular sludge for swine wastewater treatment: Implications for antibiotic and antibiotic resistance gene elimination - Meng-Yuan Li; Run-Dong Zhang; Shuang-Shuang Liu; Cheng-Lei Pei; Liang-Ying He; Jian-Liang Zhao; You-Sheng Liu; Yi-Jing Shi; Guang-Guo Ying (Bioresource Technology, 2024)

Relationship between human activities and environmental changes in the southern Tibetan Plateau since the Little Ice Age - Cunlin Li; Liping Zhu; Qingfeng Ma; Jianting Ju; Jiuju Cheng; Marco A. Aquino-López; Run Zhang; Qiangqiang Kou; Xinmiao Lü; Junbo Wang (Science of The Total Environment, 2024)

Structurally diverse diterpenoids from the seeds of Caesalpinia minax Hance and their bioactivities - Wen-Chao Tu; Lin-Fen Ding; Liu-Dong Song; Yong-Jiao Li; Run-Cheng Yan; Yun Wu; Wei-Yang Feng; Xing-De Wu (Phytochemistry, 2024)

Corrigendum to “Ionic-confining-assisted multiple-mode tunable light emitting of carbon nanodots” [Chem. Eng. J. 486 (2024) 150196] - Jing-Nan Hao; Zhong-Zheng Ding; Cheng-Long Shen; Guang-Song Zheng; Jia-Lu Liu; Ruo-Bing Li; Run-Wei Song; Kai-Kai Liu; Jin-Hao Zang; Lin Dong; Qing Lou; Chong-Xin Shan (Chemical Engineering Journal, 2024)

Occurrence and mechanism of sulfamethoxazole in alginate-like extracellular polymers from excess sludge - Chen Shi; Ming Cheng; Run-Gen Zeng; Cong-Cong Li; Qian Wang; Li-Ting Hao; Ran-Bin Liu; Xiao-Di Hao; Xiang-Yang Wang; Yuan-Yuan Wu (Bioresource Technology, 2024)

Characterization of a pangolin SARS-CoV-2-related virus isolate that uses the human ACE2 receptor - Luo-Yuan Xia; Xue-Feng Wang; Xiao-Ming Cui; Yi-Ming Zhang; Zhen-Fei Wang; En-Tao Li; Chang-Fa Fan; Ke Song; Yuan-Guo Li; Run-Ze Ye; Fang-Xu Li; Dai-Yun Zhu; et al. (Science China Life Sciences, 2024)

Anti-pancreatic cancer activity of cassane diterpenoids isolated from the seeds of Caesalpinia sappan mediated by autophagy activation via ROS/AMPK/mTORC1 pathway - Jia Su; De-Sheng Wang; Guo-Xian Hu; Yu-Yao Liu; Ming Hu; Ya Chen; Qi-Qi Wang; Run-Cheng Yan; Yun Wu; Yong-Jiao Li; Ke Ma; Yan-Yan Qi; et al. (Phytochemistry, 2024)

Identification, distribution, bactericidal and immunoregulatory activities of NK-lysins in grass carp (Ctenopharyngodon idella) - Gai Ling Wang; En Zhong Li; Da Hong Li; Ming Cheng Wang; Shan Shan Sun; Run Yan Xiong; Chuan Feng Li; Bao Jian Sun; Hai Xia Xie (Aquaculture, 2024)

Ionic-confining-assisted multiple-mode tunable light emitting of carbon nanodots - Jing-Nan Hao; Zhong-Zheng Ding; Cheng-Long Shen; Guang-Song Zheng; Jia-Lu Liu; Ruo-Bing Li; Run-Wei Song; Kai-Kai Liu; Jin-Hao Zang; Lin Dong; Qing Lou; Chong-Xin Shan (Chemical Engineering Journal, 2024)

Spatial-temporal variation of soil organic matter decomposition potential in China - Qi Chen; Zeyan Zhou; Sulin Cai; Meiqi Lv; Yinghui Yang; Yunchao Luo; Han Jiang; Run Liu; Tingting Cao; Bei Yao; Yunru Chen; Qiang Li; et al. (Soil and Tillage Research, 2024)

Green N1 additive modified perovskite precursor enables effective manufacturing of large-area solar cell modules with high efficiency and stability - Yue Zang; Yibo Tu; Chuanjia Jiao; Wangnan Li; Peng Zhou; Jiahao Cheng; Gaoyuan Yang; Tianxiang Shao; Jingchuan Ye; Guodong Li; Liang Chu; Shaojian Lu; et al. (Chemical Engineering Journal, 2024)

The role of the gut-liver axis in modulating non-alcoholic fatty liver disease through dietary patterns and microecological agents - Yucheng Fang; Ziyang Fang; Ziwei Li; Run Yu; Haimeng Zhang; Qinwen Wang; Xiangrong Cheng; Guowei Le; Guoqing Wu (Food Bioscience, 2023)

Manual correction of genome annotation improved alternative splicing identification of Artemisia annua - Zhaoyu Liu; Yupeng Du; Zhihao Sun; Bohan Cheng; Zenghao Bi; Zhicheng Yao; Yuting Liang; Huiling Zhang; Run Yao; Shen Kang; Yuhua Shi; Huihua Wan; et al. (Planta, 2023)

Suppression effects and mechanisms of three typical solid suppressants on titanium hydride dust explosions - Shi-zhou Li; Yang-fan Cheng; Rui Wang; Meng Li; Run Li; Hong-hao Ma (Process Safety and Environmental Protection, 2023)

Continuous Co-incorporation of Chinese Milk Vetch and Rice Straw with Reduced Chemical Fertilizer Maintains Rice Yield as a Consequence of Increased Carbon and Nitrogen Storage in Soil Aggregates - Rongyan Bu; Wenlong Cheng; Shang Han; Run Hu; Hui Wang; Shan Tang; Min Li; Qin Zhu; Ji Wu; Weidong Cao (Journal of Soil Science and Plant Nutrition, 2023)

LC-MS Based Metabolomic Profiling of Largehead Hairtail (Trichiurus japonicus) Ovary Reveals Metabolic Signatures of Ovarian Developmental Process (II–IV) - Liu-Ying Feng; Li-Ping Yan; Run-Wei Li; Sheng-Fa Li; Jia-Hua Cheng; Yan Jin (Fishes, 2023)
Trichiurus japonicus is an economically important fish that ranks 11th in global marine fish capture production. However, the reproductive characteristics of this fish have undergone notable changes in recent decades, potentially affecting the quality of offspring and sustainable utilization. To improve our understanding of the physiological regulation of maturation in T. japonicus, untargeted liquid chromatography mass spectrometry was utilized to identify the small molecules that characterize the comprehensive metabolic profiles of ovaries during ovary development from stage II to stage IV. According to the results of OPLS-DA, the ovarian metabolite profiles of the three developmental stages were separated. The concentrations of 124 and 100 metabolites were significantly altered between stage II vs. III and III vs. IV, respectively. Lipids and lipid-like molecules accounted for the largest proportion of the altered metabolites, followed by amino acids, peptides, and analogues. The significantly altered metabolites-enriched pathways differed slightly between stages II and III and stages III and IV. Steroid-related pathways were heavily affected during stages II to III, while significantly altered metabolites from stages III to IV were involved in oocyte-maturation-related pathways. Through metabonomics analysis, potentially important metabolic pathways and metabolites between different ovarian stages were detected, providing basic information for further investigation of maturation mechanisms in wild fish.

Peracetic acid activation via the synergic effect of Co and Fe in CoFe-LDH for efficient degradation of pharmaceuticals in hospital wastewater - Zhi-Hui Xie; Chuan-Shu He; Yong-Li He; Shu-Run Yang; Si-Ying Yu; Zhaokun Xiong; Ye Du; Yang Liu; Zhi-Cheng Pan; Gang Yao; Bo Lai (Water Research, 2023)

Research on the Critical Buckling Pressure of Bucket Foundations with Inner Compartments for Offshore Wind Turbines - Guodong Sun; Run Liu; Qingxin Li; Guoyu Huang; Zhenbo Zhou; Cheng Zhang (Journal of Ocean University of China, 2023)

A New Species of Paradiplozoon (Monogenea: Diplozoidae), A Gill Parasite of the Schizothorax Fish (Cyprinidae: Schizothoracinae) from the Yarkand River, Xinjiang, China - Kadirden Arken; Cui-Lan Hao; Ai-Ming Guo; Wen-Run Zhang; Meng-Jie Rong; Wuljan Kamal; Sheng-Li Tian; Munira Kadir; Cheng Yue (Acta Parasitologica, 2022)

Identification of differentially expressed genes associated with aluminum resistance in the soybean plant - Jing-xuan Wang; Bo Wang; Lu-bin Cui; Hao Xie; Run-zhi Li; Cheng Wang; Zhang-jie Nan; Yu-shu Liu; Jing-yu Ma; Yun-jin Sun; Wei-yu Li (Physiology and Molecular Biology of Plants, 2021)

High-throughput sequencing reveals the molecular mechanisms determining the stay-green characteristic in soybeans - Cheng Wang; Le Gao; Run Zhi Li; Ye Wang; Yang Ying Liu; Xin Zhang; Hao Xie (Journal of Biosciences, 2020)

Effect of Interaction between Adenosine and Nitric Oxide on Central Nervous System Oxygen Toxicity - Cheng-wei Xie; Zhong-zhuang Wang; Ya-nan Zhang; Yu-liang Chen; Run-ping Li; Jun-dong Zhang (Neurotoxicity Research, 2019)

Correlation between S100A11 and the TGF-β1/SMAD4 pathway and its effects on the proliferation and apoptosis of pancreatic cancer cell line PANC-1 - Yi-Fei Ji; Tao Li; Feng Jiang; Wen-Kai Ni; Cheng-Qi Guan; Zhao-Xiu Liu; Cui-Hua Lu; Run-Zhou Ni; Wei Wu; Ming-Bing Xiao (Molecular and Cellular Biochemistry, 2019)

The jasmonate-responsive transcription factor CbWRKY24 regulates terpenoid biosynthetic genes to promote saponin biosynthesis in Conyza blinii H. Lév. - Wen-Jun Sun; Jun-Yi Zhan; Tian-Run Zheng; Rong Sun; Tao Wang; Zi-Zhong Tang; Tong-Liang Bu; Cheng-Lei Li; Qi Wu; Hui Chen (Journal of Genetics, 2018)

Hydrogen Peroxide and Strigolactones Signaling Are Involved in Alleviation of Salt Stress Induced by Arbuscular Mycorrhizal Fungus in Sesbania cannabina Seedlings - Cun-Cui Kong; Cheng-Gang Ren; Run-Zhi Li; Zhi-Hong Xie; Ji-Ping Wang (Journal of Plant Growth Regulation, 2017)

Identification and characterization of multiple porcine astrovirus genotypes in Hunan province, China - Chao-Ting Xiao; Zhang Luo; Sun-Liang Lv; Tanja Opriessnig; Run-Cheng Li; Xing-Long Yu (Archives of Virology, 2017)

Gastroprotective effect of palmatine against acetic acid-induced gastric ulcers in rats - Ling Wang; Xue Wang; Su-Li Zhang; Xiao-Ming Zhu; Yan-Qi Liu; Zi-Jing Song; Wen-Juan Du; Jun Ji; Cheng-Long Cui; Xin He; Chun-Feng Zhang; Chang-Run Guo; et al. (Journal of Natural Medicines, 2017)

Transcriptome analysis reveals translational regulation in barley microspore-derived embryogenic callus under salt stress - Cheng-hong Liu; Rui-ju Lu; Gui-mei Guo; Ting He; Ying-bo Li; Hong-wei Xu; Run-hong Gao; Zhi-wei Chen; Jian-hua Huang (Plant Cell Reports, 2016)

A convenient four-component one-pot synthesis of 2-amino-1,3,4-thiadiazoles in water - Peng Liu; Ao-Ze Su; Yuan-Qiang Wang; Ze-Mei Ge; Tie-Ming Cheng; Run-Tao Li (Molecular Diversity, 2014)

High seroprevalence of Chlamydia infection in sows in Hunan province, subtropical China - Xiao-Xuan Zhang; Run-Cheng Li; Guo-Hua Liu; Wei Cong; Hui-Qun Song; Xing-Long Yu; Xing-Quan Zhu (Tropical Animal Health and Production, 2014)

RT-PCR test for detecting porcine sapovirus in weanling piglets in Hunan Province, China - Guo-Hua Liu; Run-Cheng Li; Ze-Bin Huang; Jun Yang; Chao-Ting Xiao; Jing Li; Man-Xiang Li; Yun-Qiu Yan; Xing-Long Yu (Tropical Animal Health and Production, 2012)

An efficient three-component, one-pot synthesis of 2-alkylthio-4-amino-5-cyano-6-aryl(alkyl)pyrimidines in water - Qiao-Yan Li; Ze-Mei Ge; Tie-Ming Cheng; Run-Tao Li (Molecular Diversity, 2012)

Seroprevalence of porcine cytomegalovirus and sapovirus infection in pigs in Hunan province, China - Guo-Hua Liu; Run-Cheng Li; Jing Li; Ze-Bin Huang; Chao-Ting Xiao; Wei Luo; Meng Ge; Da-Liang Jiang; Xing-Long Yu (Archives of Virology, 2012)

Comparative ecophysiological responses to drought of two shrub and four tree species from karst habitats of southwestern China - Chang-Cheng Liu; Yu-Guo Liu; Ke Guo; Guo-Qing Li; Yuan-Run Zheng; Li-Fei Yu; Rui Yang (Trees, 2011)